Performance analysis of OFDM receiver with modified PTS technique. (2016) - Thanigasalam, M.; Dananjayan, P.
Modified partial transmit sequence (PTS) technique with adjacent partitioning and four phase factors is implemented to enhance the PAPR performance of OFDM system and its PAPR reduction performance is evaluated in terms of the complementary cumulative distribution function (CCDF). A multipath fading environment is considered and the performance of the OFDM receiver is evaluated using least square (LS) and minimum mean square error (MMSE) channel estimation methods. The performance of the receiver is evaluated in terms of mean square error (MSE) and bit error rate (BER). The performance of the OFDM receiver is enhanced with PAPR reduction.